1997
DOI: 10.1046/j.1365-2125.1997.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of rocuronium in patients with hepatic cirrhosis

Abstract: Aims To determine the effects of hepatic cirrhosis on the pharmacodynamics and pharmacokinetics of rocuronium bromide. Methods We studied 21 healthy patients and 17 patients with mild or moderate cirrhosis (Child-Pugh Class A and B). Patients were premedicated with diazepam orally; anaesthesia was induced with fentanyl and thiopentone, and maintained with isoflurane 0.6% (end-tidal) and nitrous oxide 66% in oxygen. The compound action potential of the adductor pollicis muscle in response to supramaximal stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 2 publications
(2 reference statements)
0
48
0
1
Order By: Relevance
“…12 Although we did not measure rocuronium and dexamethasone plasma concentrations, they were likely less concentrated than sugammadex plasma concentrations based on the doses used and their respective pharmacokinetic characteristics. 13,14 Nonetheless, it is important to point out that a proper comparison with previous finding in vitro is difficult, given that in vitro concentrations are likely more comparable with tissue concentrations rather than plasma concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…12 Although we did not measure rocuronium and dexamethasone plasma concentrations, they were likely less concentrated than sugammadex plasma concentrations based on the doses used and their respective pharmacokinetic characteristics. 13,14 Nonetheless, it is important to point out that a proper comparison with previous finding in vitro is difficult, given that in vitro concentrations are likely more comparable with tissue concentrations rather than plasma concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…However, because rocuronium was mostly metabolized in the liver and excreted through bile [4], the duration of neuromuscular blockade of rocuronium may be prolonged in patients with liver and kidney failure [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…However, animal studies have suggested that rocuronium is mostly metabolized in the liver and excreted through bile, and less than 10% of the unchanged form after a bolus administration is detected in cat urine in 24 hours 23. The duration of neuromuscular blockade of rocuronium at an equipotent single dose may be prolonged and variable in patients with liver and kidney failure 24,25. In this respect, cisatracurium is metabolized by Hoffmann elimination to laudanosine and is recommendable in patients with liver and kidney failure.…”
Section: Discussionmentioning
confidence: 99%